PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MEMBACA AKSARA JAWA DENGAN TEKNIK K-W-H-L-W PADA SISWA KELAS VIII C SMPN 2 MAGELANG SEMESTER 2 TAHUN PELAJARAN 2013/2014 - Diah Kusumaning Bratangalun (TRANSFORMATIKA, 2015)
The low interest of student in teaching and learning to read Javanese scripts can result in the learning process becomes less than optimal so that the result are not up to it.It shows that if we want to improvestudent learning outcomes, then we should be able to increase the activeness of students on the subject studied. Based on this background, the researchers wanted to examine the relationship between k-w-h-l-w techniques in improving activeness and learning achievement of reading Javanese scripts through k-w-h-l-w technique to the eight grade students for â€œCâ€ class of SMP 2 Magelang in second semester in the school year 2013/2014.The subject of the research of the research are 22 student consisted of 14 girls and 8 boys. They aredivided into big group and small one. The problem of this research can be formulated: Can k-w-h-l-w tehnique improve activeness and learning achievement of reading Javanese scripts through k-w-h-l-w tehnique to the eight grade students for â€œCâ€ class of SMP 2 Magelang?The research carried out in February- May 2014. It was conducted in three cycles. Performed at each cycle(1 meeting) made observations of the students during the learning activities using instrumental observations, evaluated student responses to the questionnaire and evaluated activities using teacherâ€™s questionnaires, each cycle consists of four phases: planning, acting, observing and reflecting.The result of the research : (1) k-w-h-l-w tehnique can improve the activiness of enough criteria (2,23) becames high Â criteria (2,97) or Â 0,74 (33,18%) and (2) k-w-h-l-w tehnique can improve learning achievement Â from less category (56,77) becames good category (84,84 or 28,07 (49,45%).Its conclusion obtained from the study of this class action is that k-w-h-l-w tehnique is the achievement of the k-w-h-l-w tehnique can improve the studentsâ€™ activiness and learning achieviement to read Javanese script.Â Keyword: K-W-H-L-W tehnique, Javanese scripts, activiness, learning achievement